Cytomegalovirus infection and IQ in patients with severe mental illness and healthy individuals. (June 2021) - Andreou, Dimitrios; Jørgensen, Kjetil Nordbø; Wortinger, Laura A.; Engen, Kristine; Vaskinn, Anja; Ueland, Torill; Yolken, Robert H.; Andreassen, Ole A.; Agartz, Ingrid
Highlights: Cytomegalovirus infection is associated with lower general intelligence in women but not men with schizophrenia spectrum disorders. Cytomegalovirus infection is associated with higher general intelligence in men but not women with bipolar spectrum disorders. Cytomegalovirus infection is not associated with general intelligence in healthy controls. Abstract: Cytomegalovirus (CMV) infection in immunocompetent adults is usually asymptomatic, but results in lifelong latency. Infection occurring congenitally or in immunodeficiency can lead to cognitive impairment. We aimed to investigate the associations between CMV exposure and intelligence quotient (IQ) in patients with schizophrenia spectrum disorders (SZS), bipolar spectrum disorders (BDS) and healthy controls (HC). CMV immunoglobulin G antibody concentrations were measured by immunoassay and expressed as dichotomous measures (seropositive/CMV+ vs. seronegative/CMV-). Based on a significant CMV-by-diagnosis-by-sex interaction on IQ, we investigated main and interaction effects of CMV and sex on IQ in each diagnostic category. Significant CMV-by-sex interactions were found in patient groups. In SZS, CMV+ female patients (n = 50) had significantly lower IQ than CMV- female patients (n = 33), whereas CMV+ (n = 48) and CMV- (n = 45) male patients did not differ in IQ. In BDS, CMV+ (n = 49) and CMV- (n = 37) female patients did not differ in IQ, whereas CMV+ male patients (n = 33) had significantly higher IQ than CMV- male patients (n = 32). Among HC, CMV+ (n = 138) and CMV- (n = 118) male participants as well as CMV+ (n = 125) and CMV- (n = 93) female participants did not differ in IQ. Our findings suggest that CMV exposure may affect IQ in patients with severe mental illness but not HC.